Application of TENIS and artificial neural networks in neutron spectroscopy for BNCT beams in IRT-T and TRR: additional research; European Physical Journal Plus; Vol. 140 - Kazemi Z. Zeinab; Rahmani F. Faezeh; Ghal-Eh N. Nima; Bedenko S. V. Sergey Vladimirovich (2025, 2025)
Title screen